The Arabidopsis U–box/ARM repeat E3 ligase AtPUB4 influences growth and degeneration of tapetal cells, and its mutation leads to conditional male sterility. (15th March 2013) - Wang, Hai; Lu, Yuqing; Jiang, Tiantian; Berg, Howard; Li, Cong; Xia, Yiji
Summary Pollen formation is a complex developmental process that has been extensively investigated to unravel underlying fundamental developmental mechanisms and for genetic manipulation of the male‐sterility trait for hybrid crop production. Here we describe identification of AtPUB4, a U–box/ARM repeat‐containing E3 ubiquitin ligase, as a novel player in male fertility in Arabidopsis. Loss of AtPUB4 function causes hypertrophic growth of the tapetum layer. The Atpub4 mutation also leads to incomplete degeneration of the tapetal cells and strikingly abnormal exine structures of pollen grains. As a result, although the Atpub4 mutant produces viable pollen, the pollen grains adhere to each other and to the remnants of incompletely degenerated tapetal cells, and do not properly disperse from dehisced anthers for successful pollination. We found that the male‐sterility phenotype caused by the Atpub4 mutation is temperature‐dependent: the mutant plants are sterile when grown at 22°C but are partially fertile at 16°C. Our study also indicates that the AtPUB4‐mediated pathway acts in parallel with the brassinosteroid pathway in controlling developmental fates of the tapetal cells to ensure male fertility.